2021
DOI: 10.48550/arxiv.2111.11508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct Constraints on the Extremely Metal-Poor Massive Stars Underlying Nebular C IV Emission from Ultra-Deep HST/COS Ultraviolet Spectroscopy

Peter Senchyna,
Daniel P. Stark,
Stephane Charlot
et al.

Abstract: Metal-poor nearby galaxies hosting massive stars have a fundamental role to play in our understanding of both high-redshift galaxies and low metallicity stellar populations. But while much attention has been focused on their bright nebular gas emission, the massive stars that power it remain challenging to constrain. Here we present exceptionally deep Hubble Space Telescope ultraviolet spectra targeting six galaxies that power strong nebular C IV emission approaching that encountered at 𝑧 > 6. We find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(167 reference statements)
1
1
0
Order By: Relevance
“…fig. 7 in Senchyna et al 2021). The residuals of the UV continuum are comparable with the statistical errors of the data.…”
Section: Stellar Populations Of the Three Knots Based On Spectroscopysupporting
confidence: 71%
“…fig. 7 in Senchyna et al 2021). The residuals of the UV continuum are comparable with the statistical errors of the data.…”
Section: Stellar Populations Of the Three Knots Based On Spectroscopysupporting
confidence: 71%
“…They are low-mass low-metallicity galaxies at z ∼ 0.01 that both show very strong C iv emission with EW(C iv) ∼ 6 − 10 Å (Berg et al 2019b,a). Based on high-resolution COS spectra, which show strong nebular C iv emission in the two doublet lines and indications for minor radiation transfer effects in these lines, Berg et al (2019a) have suggested that J104457 is optically thin to ionizing radiation, at least at energies above 47.9 eV, the ionization potential of C 3+ (see also Senchyna et al 2021). It also shares other properties of strong LyC leakers, such as a very high O32= 16.2.…”
Section: Strong Lyc Leakers Show Strong C Iv λ1550 Emission and A Hig...mentioning
confidence: 99%